Far-right anniversary politics and social media: The Alternative for Germany's contestation of the East German past on Twitter. (December 2022) - Richardson-Little, Ned; Merrill, Samuel; Arlaud, Leah
This article examines how the German radical-right populist party the Alternative for Germany ( Alternative für Deutschland ) and its politicians have engaged with the public memory of the East German past via Twitter and how this has impacted the use of social media as a tool of political commemoration in Germany. The article analyses the mnemonic wars over 'anniversary tweets' related to four events: the East German Uprising (1953); the construction (1961) and fall (1989) of the Berlin Wall; and German reunification (1990). The article surveys when and how Twitter became a platform for these events' political commemoration and the role of the Alternative für Deutschland therein. It also outlines the mnemonic discourses that the Alternative für Deutschland has deployed on Twitter around these events' anniversaries and explores the sorts of digital contestation and transnationalization evident at these times.